마리야에서 보치카료바로, 보치카료바에서 야시카로 : 여성결사대대 지휘관 마리야 보치카료바의 삶과 자서전 『야시카』 - 柳翰秀; Lyu Hansu (중소연구, 2023)
마리야 보치카료바라는 여성은 러시아 현대사에서 매우 독특한 인물이다. 유형수인 배우자를 따라 시베리아에서 지내던 보치카료바는 제1차 세계대전이 일어나자 자원해서 군대에 들어가서 훈련을 마치고 러시아군 병사가 되어 최전선에서 싸웠으며, 1917년 혁명기에는 싸우기를 거부하는 남성 병사들을 부끄럽게 만들어 싸우게 만들 목적으로 여성결사대대를 편성해서 조련했고 실전에서 지휘했다. 10월 혁명의 여파 속에서 여성결사대대가 해체된 뒤에 보치카료바는 미국과 영국으로 건너가 볼셰비키 정권을 물리칠 간섭군을 러시아에 보내라고 요청했다. 러시아에 돌아온 보치카료바는 반혁명 운동에 가담했다 체포되어 1919년에 총살되었다. 보치카료바는 1918년 여름에 미국에서 자기의 삶을 구술해서 영어로 씌어진 자서전 『야시카』를 펴냈다. 『야시카』에는 진솔한 고백과 내면의 토로, 사건의 진실과 지난날의 생생한 재현이 들어 있는 한편으로 오류와 혼동, 누락과 과장, 왜곡과 허위도 섞여 있다. 따라서 『야시카』는 소중하지만 신중하게 다뤄야 할 사료이다. 『야시카』에 들어있는 진실을 가리거나 그 진실과 뒤섞인 오류와 혼동, 누락과 과장, 왜곡과 허위를 걷어내거나 걸러내야 한다. 다시 말해서, 엄정한 사료 비판의 대상이 되어야 한다. 모든 자서전과 회고록이 그렇듯이, 보치카료바의 자서전은 엄정한 비판과 신중한 접근이 이루어져야만, 역사의 진실을 밝혀주는 사료가 될 수 있다. This article aims to illuminate the life of Maria Bochkareva, the commander of the First Russian Women’s Battalion of Death and to review her autobiography Yashka: My Life as Peasant, Exile and Soldier. Bochkareva is a very unique figure in the modern history of Russia. When the First World War broke out, Bochkareva who lived in Siberia with her spouse in exile volunteered to join the Russian army, completed the military training to be a regular soldier, and fought the enemy on the front lines. During the revolutionary process of 1917, she organized and trained the Women’s Battalion of Death with a view to convincing the male soldiers to fight by making them ashamed, and then commanded the battalion in the actual battles. After the Women’s Battalion of Death was disbanded in the aftermath of the October Revolution, Bochkareva went to the United States and England to ask for the intervention force to be sent to Russia and to defeat the Bolshevik regime. 1919 saw that Bochkaleva who returned to Russia and joined the counter-revolutionary movement in Siberia was arrested and shot by the Bolsheviks. While in the United States in 1918, Bochkareva dictated her life story and published her autobiography Yashka written in English. This text contains the sincere confessions, the inner revelations, the truth of the events and the vivid reproductions of the past, while there are some errors and confusions, some omissions and exaggerations, and a number of distortions and falsehoods. Therefore, Yashka is an important and precious historical source that needs to be handled carefully. Errors and confusion, omissions and exaggerations, distortions and falsities mixed with the truths must be removed or filtered out. In a nutshell, Yashka should be subject to the strict source criticism. As with all autobiographies and memoirs, Yashka could be a source of historical truth only when it is subject to strict criticism and careful approach.